Analysis on Sentence Structure in Lewis Carrol’s Alice’s Adventures in Wonderland - Lisa Ma'rufi; Sudarsono; Syarif Husin; Eusabinus Bunau; Ikhsanudin (Kirana Publisher (KNPub), 2023)
The purpose of this research is to identify types of sentences and their frequency contained in the novel Alice’s Adventures in Wonderland in order to help high school students to improve their ability in understanding and practicing English sentence structure. This research was a descriptive study. The corpus of this research was the novel “Alice’s Adventures in Wonderland” which is written by Lewis Carroll. All of the declarative sentences of the conversation in all of the novel's chapters were analyzed in this research which include formal and informal sentences, direct sentences, and nominal and verbal sentences. This research used open coding and focused coding as the procedure of data analysis. The corpus was sorted for complete declarative sentences. After that, they were grouped and coded based on their types of sentences and subcategories. Then, each type of sentence’s frequency of occurrence was calculated. The finding found that there are four sentence types used by the novel, which are: simple sentences, compound sentences, complex sentences, complex sentences, and compound-complex sentences. The total declarative sentences found are 440 sentences. Simple sentence becomes the most frequent sentence type used by the novel and complex compound sentence becomes the least. This research covered the information for students about sentence types they need to master before reading the novel as one of their media to learn and practice sentence structure.